Effect of cadmium chloride during larval development of American bullfrog Lithobates catesbeianus (Shaw, 1802) - Gastelum, Ana; Aquino, Abraham; Aldama, Lauro (Acta Universitaria, 2019)
American bullfrog tadpoles were exposed to laboratory conditions at five concentrations (0.05 mg/L, 0.10 mg/L, 0.125 mg/L, 0.15 mg/L and 0.175 mg/L) of cadmium chloride, in order to determine the median lethal concentration (LC50) and the effects on the liver tissue during larval development. Sixty tadpoles in Gosner’s 21-25 stages were placed in two liters of water with different concentrations of metal for 96 hours, using 10 individuals per container with each metal concentration. Essays were repeated twice. Once tests were completed, the livers were extracted for conventional histology analysis. The concentration corresponding to 50% mortality of the larvae obtained by the EPA Probit software was 0115 mg/L. The histological analysis showed a greater cell damage as concentrations of metal were increasing. Therefore, it was determined that these organisms are sensitive to low concentrations of cadmium chloride.